2007
DOI: 10.1016/j.seizure.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection in epileptic patients

Abstract: It is well known that there might be an epidemiological association between Helicobacter pylori infection and extraintestinal diseases. This study aimed at determining H. pylori infection in epileptic patients. Forty-seven cryptogenic epileptic patients (Group 1) and 35 healthy people (Group 2) participated in this study. Presence of H. pylori infection was examined by H. pylori stool antigen (HpSA), H. pylori IgG, and IgM. HpSA was detected in 21 participants (44.6%) in Group 1 and in 3 participants (8.5%) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Recent studies showed an association between Helicobacter pylori infection ( Hp ‐I) and epilepsy, especially with poor prognosis [2]. Moreover, using histology, the practical gold standard for current Hp ‐I diagnosis, we showed a strong association between Hp ‐I and MS in a Greek cohort [3].…”
mentioning
confidence: 82%
“…Recent studies showed an association between Helicobacter pylori infection ( Hp ‐I) and epilepsy, especially with poor prognosis [2]. Moreover, using histology, the practical gold standard for current Hp ‐I diagnosis, we showed a strong association between Hp ‐I and MS in a Greek cohort [3].…”
mentioning
confidence: 82%
“…H. pylori infection has also been found to be associated with epilepsy, especially in patients with poor prognosis 73 . However, as this is a small sample study, routine checking for H. pylori is not recommended.…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…There is a possible association of H. pylori infection with different seizure disorders 46,47 . Okuda et al investigated the rate of H. pylori infection in patients with epilepsy and seizure disorder 46 .…”
Section: Seizure Disordersmentioning
confidence: 99%
“…Ozturk et al studied the presence of H. pylori infection in seizure patients for the possible trigger effect of seizure via immunological mechanisms 47 . Their findings supported that H pylori infection might trigger epilepsy by immunological mechanisms as shown by other studies before 47 . They proposed that H. pylori stool antigen test can be used to identify active H pylori infections in patients with seizure disorders.…”
Section: The Production Of Autoantibodies Due To the Cross-mimicry mentioning
confidence: 99%